The Influence of Information Search Learning Strategies and Student Learning Motivation on Learning Outcomes in PAI Learning - Rizki Abdina Mawaddah; Ali Imran Sinaga; Salim Salim (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
This study aims to determine the influence of the application of Information Search learning strategies and learning motivation on PAI learning outcomes of SMA Negeri 1 Merbau students as well as the interaction between learning strategies and learning motivation on PAI learning outcomes. This research is a quantitative study with a population of as many as all class XI students at SMA Negeri 1 Merbau consisting of 6 study groups. Based on the Cluster Random Sampling technique, one is an Information Search learning class and one is an Expository learning class. The instruments of this study are tests and questionnaires. The test of normality of the learning outcomes data is the Liliefors test, and the homogeneity test is the Fisher test and the Bartlett Test. The data analysis technique is a two-path Anava at a significant α = 0.05 followed by the Schiche test. The results showed that there was a shift in the Information Search learning strategy on the learning outcomes of PAI students of SMA Negeri 1 Merbau with high (X̅= 28.6) and Low (X̅=19.6) learning motivations. In this case, the PAI learning outcomes of students with high motivation are higher than those of pai students with low learning motivation.